A pilot randomized controlled trial of on-line interventions to improve sleep quality in adults after mild or moderate traumatic brain injury. (May 2018) - Theadom, Alice; Barker-Collo, Suzanne; Jones, Kelly; Dudley, Margaret; Vincent, Norah; Feigin, Valery
Objective: To explore feasibility and potential efficacy of on-line interventions for sleep quality following a traumatic brain injury (TBI). Design: A two parallel-group, randomized controlled pilot study. Setting: Community-based. Subjects: In all, 24 participants (mean age: 35.9 ± 11.8 years) who reported experiencing sleep difficulties between 3 and 36 months after a mild or moderate TBI. Interventions: Participants were randomized to receive either a cognitive behaviour therapy or an education intervention on-line. Both interventions were self-completed for 20–30 minutes per week over a six-week period. Main measures: The Pittsburgh Sleep Quality Index assessed self-reported sleep quality with actigraphy used as an objective measure of sleep quality. The CNS Vital Signs on-line neuropsychological test assessed cognitive functioning and the Rivermead Post-concussion Symptoms and Quality of Life after Brain Injury questionnaires were completed pre and post intervention. Results: Both programmes demonstrated feasibility for use post TBI, with 83.3% of participants completing the interventions. The cognitive behaviour therapy group experienced significant reductions ( F = 5.47, p = 0.04) in sleep disturbance (mean individual change = −4.00) in comparison to controls post intervention (mean individual change = −1.50) with a moderate effect size of 1.17. There were no significant group differences on objective sleep quality, cognitive functioning, post-concussion symptoms or quality of life. Conclusion: On-line programmes designed to improve sleep are feasible for use for adults following mild-to-moderate TBI. Based on the effect size identified in this pilot study, 128 people (64 per group) would be needed to determine clinical effectiveness.